Using hydrogen peroxide as a bladder irrigation solution for clot evacuation - Mahdi Bagheri; Mamak Tahmasebi; Sheyda Najafi; Zahra Jahangard Rafsanjani (Research Center for Rational Use of Drugs (RCRUD), 2017)
Gross hematuria or macroscopic hematuria is a high risk urologic condition that might occur in different settings. In the case of continued gross hematuria, blood clot size may grow and lead to complete obstruction of urinary outflow. Placement of three-way catheter, continuous bladder irrigation with normal saline, and cystoscopy are conventional treatments. Here we introduce a case with urinary obstruction who did not respond to conventional therapies. A subject of Hodgkin lymphoma with urinary obstruction caused by heavy gross hematuria was presented to emergency department. Three-way catheter was inserted to facilitate urination. However, there was no urinary drainage and bladder was distended. Consequently, 100 ml solution of hydrogen peroxide 0.15% was prepared and administered into the bladder to irrigate and evacuate the clots. A single intravesical infusion of hydrogen peroxide rapidly resolved urinary obstruction and improved patient distress. After administration of hydrogen peroxide solution, blood clots and bloody urine were evacuated successfully. These findings suggest that an intravesical injection of hydrogen peroxide can induce dissolution of blood clots and may be a simple and efficient therapy for urinary obstruction due to gross hematuria.